The medical and rehabilitative management of persons with motor neuron disease. - Marett, Colette Lea (My University, 2009)
Although the management of Motor Neuron Disease (MND) remains devoid of a cure, persons affected by this devastating condition are nonetheless entitled to the best quality care that is available. A paucity of information exists documenting the perceptions of healthcare consumers regarding the management that is provided. In addition optimal healthcare comprises an intricate interaction of patient-centred care, patient-centred communication, and bioethical practice, and when these three dimensions are implemented according to acceptable standards, high-quality healthcare is perceived by the healthcare consumer. Given however the socio-political challenges that face healthcare systems, the management of MND needs to be considered against current trends in service delivery and the need for evidence-based medicine. An exploratory study was therefore conducted to investigate the perceptions of persons with MND and their family members regarding current medical and rehabilitative management. The sample comprised six persons with MND who presented with a communication impairment, as well as six family members. Participants’ perceptions were elicited through the use of a semi-structured interview schedule, and questions focused on healthcare professionals’ behaviours during healthcare encounters. In addition emphasis was placed on the potential of the communication impairment to influence management. A standardised dysarthria assessment was conducted to characterise the nature of the speech impairment in each person with MND. Qualitative responses obtained from the interviews were analysed in accordance with a matrix-based approach, while quantitative data from the dysarthria assessment were analysed using descriptive statistics. Despite individual variability, perceptions of both persons with MND and their family members revealed general dissatisfaction with regard to medical and rehabilitative management. The majority of persons with MND were not referred for intervention following diagnosis, and the recommended team approach for the management of MND was absent. In addition the bioethical practice of many healthcare professionals was deemed questionable, and the communication impairment was perceived to impose a significant burden on the healthcare encounter. Furthermore all participants perceived a lack of available support systems for persons with MND, and it was thus not uncommon for individuals to pursue complementary and alternative medicine. South Africa’s current healthcare climate also appeared to further limit healthcare for this clinical population. In an attempt to improve the management of MND, implications are provided in terms of health communication, intervention, bioethical practice, and support systems. A proposed new framework of ideal service delivery for healthcare consumers of MND management is also presented. Further implications are outlined with regard to the need for innovative models of service delivery in South Africa’s healthcare context, as well as the role of speech-language pathologists, other healthcare professionals, policy makers, and educators in the improvement of the medical and rehabilitative management of MND. Finally theoretical implications and implications for future research are also documented.
Keywords: Motor Neuron Disease; Rehabilitation